Analisis Penerimaan Sistem E-Commerce Smartschool Menggunakan Model Unified Theory of Acceptance and Use of Technology - Akram Farrasanto; Muhammad Najamuddin Dwi Miharja; Nanang Tedi Kurniadi (Bulletin of Computer Science Research, 2026)
The conventional school uniform purchasing process still faces various obstacles, such as limited service time, inefficient transaction recording, and minimal real-time transaction documentation. Therefore, to overcome these problems, SMK Bina Patriot implemented the SmartSchool e-commerce system as a transaction medium for purchasing school uniforms. This study aims to analyze user acceptance of the SmartSchool e-commerce system using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The UTAUT model is used to test the effect of Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions on Behavioral Intention in using the system. This study uses a quantitative approach by using data collection techniques through distributing questionnaires to 55 students as respondents in the study. Then the resulting data will be analyzed using multiple linear regression to determine the effect of each variable on the intention to use the system. The results of this study also show that Performance Expectancy has a significant effect on Behavioral Intention with a significance value of 0.037 (p < 0.05), while Social Influence also has a significant effect with a significance value of 0.002 (p < 0.05). Conversely, Effort Expectancy did not significantly influence Behavioral Intention, with a significance value of 0.667 (p > 0.05). Therefore, it can be seen that the variable with the most dominant influence is Social Influence, with a regression coefficient of 0.4882. This study contributes to extending the application of the UTAUT model within the context of school e-commerce systems at the secondary education level, which remains relatively underexplored in existing research. Furthermore, the findings of this study can serve as a reference for schools in designing implementation strategies and developing e-commerce systems that better align with users' needs and expectations